2014
DOI: 10.1021/la502945k
|View full text |Cite
|
Sign up to set email alerts
|

Multiblock Copolymer Solutions in Contact with a Surface: Self-Assembly, Adsorption, and Percolation

Abstract: Amphiphilic copolymers are often used as compatibilizing or stabilizing agents, either in solution or at surfaces. In the special case of multiblock copolymers the connectivity of the blocks combines with the antagonistic behavior of the different types of blocks. Here we report on the behavior of solutions of amphiphilic multiblock copolymers with a large number of blocks and a low fraction of solvophobic monomers in contact with an attractive surface. Using lattice Monte Carlo simulations, the influence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Studies performed at high polymer concentrations are more scarce and therefore difficult to compare with. Recently, Hugouvieux and Kolb reported a simulation study detailing the structure of adsorbed films of multiblock copolymers at the bilayer/fluid interface over a wide range of polymer concentrations. The authors showed that micellar aggregates can adhere at the surface of lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed at high polymer concentrations are more scarce and therefore difficult to compare with. Recently, Hugouvieux and Kolb reported a simulation study detailing the structure of adsorbed films of multiblock copolymers at the bilayer/fluid interface over a wide range of polymer concentrations. The authors showed that micellar aggregates can adhere at the surface of lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…They have been successfully used for the solution of a number of topics in almost all fields of polymer science. The number of simulation papers is very high, and it is why we included only several interesting papers published recently to demonstrate progress in this field and further we focus only on articles devoted directly to the studied topic. The behavior of various polymer chains close to planar surfaces, in narrow slits and in the pores, and the mechanism of the chromatographic separation of polymer chains have already been studied theoretically by scaling approaches, , by mean-field calculations, and particularly by lattice Monte Carlo (MC) simulations. A number of individual studies concerning the effects of chain architecture , and flexibility, , molar mass, polymer concentration, , solvent quality, temperature, , polymer–wall interaction, ,, and smoothness versus roughness of the surface have been published recently.…”
Section: Introductionmentioning
confidence: 99%
“…In more concentrated solutions, decreasing the quality of the solvent and increasing the concentration of polymers gives rise to different structural regimes, from a homogeneous solution to a percolating network of core-shell micelles [29] (see Fig. 5), which can be in equilibrium with a 2D percolating network of micelles when the solution is in contact with a hydrophobic surface [30] (see Fig. 4a).…”
Section: Selected Case Studies 241 Self-assembly and Phase-space Ementioning
confidence: 99%